Mode Shape-Based Damage Localization in Steel Plates Using a Detection Index Based on 2D Wavelet Analysis - Mohtasham Khanahmadi; Majid Gholhaki; Omid Rezaifar; Adel Younesi (Journal of Rehabilitation in Civil Engineering)
Structures are subjected to a variety of environmental and loading conditions over time, and minor damage to structural elements may occur. By timely identifying damage and repairing damaged locations, it is possible to prevent the spread and development of damage to other elements and, as a result, the overall destruction of the structure. This article discusses the identification and determination of the location of damage in steel plates based on the use of the primary and secondary shapes of vibration modes and the analytical method of two-dimensional wavelet analysis. Modelling and frequency analysis of the plate were performed in ABAQUS software, and the primary and secondary mode shapes were extracted. To determine the location of the damage, a damage detection index (DDI) was proposed based on the angle between the primary and secondary mode shape vectors and the diagonal detail coefficients obtained from the wavelet analysis of the primary and secondary mode shapes. The results showed that by using this index, damage can be identified by identifying peaks resulting from irregularities and disturbances. Also, the DDI value of the damage was dependent on the severity of damage occurring in a damaged situation, and the height of the disorder peaks increased with increased damage only at that damage position.